TINJAUAN LITERATUR: TANTANGAN PEREKONOMIAN DI ERA DIGITALISASI - Vera Paulin Kay (P3M Politeknik Negeri Ambon, 2025)
Digitalization has become a major driving force in the transformation of the global economy, bringing new opportunities as well as complex challenges. This article examines the economic challenges in the era of digitalization, including the digital divide, cybersecurity, and changes in the labor market. The digital divide, encompassing access, usage, and impact of information and communication technology (ICT), can exacerbate economic inequality and hinder growth. Additionally, the increasing threat of cybersecurity demands organizations to invest in technology and training to protect sensitive data and information. Changes in the labor market due to automation and digitalization also require new skills, creating challenges for a workforce that is unprepared. To address these challenges, this article recommends a series of strategies, including investment in digital infrastructure, reform of education and training, digital inclusion policies, enhancement of cybersecurity, collaboration between the public and private sectors, and community engagement. With the right measures, it is hoped that the potential of the digital economy can be maximized and existing risks minimized, creating a more inclusive and sustainable economy. Keywords: Digitalization, Digital Divide, Cybersecurity, Labor Market, Education, Digital Inclusion